2018
DOI: 10.1016/j.ijheatmasstransfer.2017.10.070
|View full text |Cite
|
Sign up to set email alerts
|

Single-phase mixed convection of developing and fully developed flow in smooth horizontal circular tubes in the laminar and transitional flow regimes

Abstract: Highlights• Three laminar regions: Forcedand Mixed Convection Developing and Fully Developed. • Thermal entrance length correlations for forced and mixed convection laminar flow. • Local and average laminar Nusselt number correlations for mixed convection flow. • Influence of free convection on the laminar-turbulent transition. ABSTRACT Correlations to calculate the local and average heat transfer coefficients for single-phase laminar flow through horizontal circular tubes with a constant heat flux boundary co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
50
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 81 publications
(141 citation statements)
references
References 47 publications
(113 reference statements)
9
50
1
1
Order By: Relevance
“…The computationally obtained results converge with decreasing the mesh size in both, the dimensionless radial temperature distribution and the Nusselt number. The analytical solution for the Nusselt number Nu = 4.36 is also correctly evaluated and the computational results for the Nusselt number are in very good agreement with the experimental results in [38] and also the empirical result from [41]. The computed local Nusselt number and the dimensionless radial temperature profile in the pipe cross-section are plotted in Figure 4.…”
Section: Verification Of the Computational Modelsupporting
confidence: 66%
See 2 more Smart Citations
“…The computationally obtained results converge with decreasing the mesh size in both, the dimensionless radial temperature distribution and the Nusselt number. The analytical solution for the Nusselt number Nu = 4.36 is also correctly evaluated and the computational results for the Nusselt number are in very good agreement with the experimental results in [38] and also the empirical result from [41]. The computed local Nusselt number and the dimensionless radial temperature profile in the pipe cross-section are plotted in Figure 4.…”
Section: Verification Of the Computational Modelsupporting
confidence: 66%
“…This is a consequence of the assumption that the effects of the forced heat convection are predominant in comparison to the natural heat convection. This assumption is justified for cases where the flow is constrained to small geometries, such as the one used here (tube with 4 mm inner diameter), whereas the natural heat convection effects become important in larger geometries [38].…”
Section: Governing Transport Equations and Constitutive Relationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, this correlation is suited for forced convection conditions, rather than mixed convection conditions. This paper forms part of a bigger study and is complimentary to papers published by Meyer and Everts [1] and Everts and Meyer [34,36]. Meyer and Everts [1] investigated mixed convection laminar flow, as well as the effect of free convection on the laminarturbulent transition along the tube length.…”
Section: Introductionmentioning
confidence: 86%
“…Another limitation of this approach is that the laminar Nusselt number correlation is for developing forced convection flow and therefore produces a Nusselt number of 4.36 for fully developed flow. In most cases this will not be correct as laminar flow are normally dominated by mixed convection [1], especially when low Prandtl number fluids, such as water, are used. Although this method was tested using the numerical data of Abraham et al [35], Gnielinski [33] mentioned that "no experimental data were found which have allowed checking the Nusselt numbers obtained by the calculation procedure outlined above in the region of linear interpolation, i.e., between 1 000 < Re < 4 000".…”
Section: Introductionmentioning
confidence: 99%